A tale of two Basque reciprocal anaphors in Basque: preliminaries - Xabier Artiagoitia (Fontes Linguae Vasconum, 2018)
This article provides a typological perspective of Basque reciprocal expressions and reviews previous accounts of the difference between the Basque reciprocal anaphors elkarand bata bestea ‘each other, one another’. Moreover, it presents abundant data drawn from the Basque literary tradition to show that Rebuschi’s (1988, 1989) first account is in fact correct and that the predictions made by his later (1993) account regarding the distribution of bata bestea are not fulfilled. The overview of the usage patterns for bata bestea throughout the Basque literary tradition also confirms a high degree of homogeneity across dialects and periods. The article closes introducing further syntactic and interpretive differences between the two reciprocal anaphors, which should set the basis for a future account.